Unveiling the Antibacterial Properties of Statins: An In Vitro Study on Helicobacter pylori - Manijeh Ebrahimzadeh; Fariba Asgharpour; Javad Shokri Shirvani; Sohrab Kazemi; Ali Akbar Moghadamnia (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Helicobacter pylori (H. pylori), a widespread bacterial pathogen, is associated with various gastrointestinal diseases, including gastric cancer. Statins, widely prescribed cholesterol-lowering agents, have demonstrated pleiotropic effects, including potential antimicrobial properties. This in vitro study investigated the direct antibacterial effects of three clinically approved statins, simvastatin, atorvastatin, and rosuvastatin, against H. pylori isolates. Methods. H. pylori strains were isolated from gastric biopsies of dyspeptic patients and identified by microbiological techniques. The minimum inhibitory concentrations (MICs) of statins were determined using the agar dilution method, and their antimicrobial activity was evaluated by the disc diffusion method using different concentrations of simvastatin, atorvastatin, rosuvastatin, tetracycline, and amoxicillin. Scanning electron microscopy (SEM) was employed to examine the morphology of H. pylori cells. Results. The minimum inhibitory concentration (MIC) values (μg/mL) of atorvastatin, rosuvastatin, simvastatin, tetracycline, and amoxicillin against H. pylori were 240 ± 20, 450 ± 20, 460 ± 15, 155 ± 30, and 140 ± 20, respectively. In the disc diffusion assay, atorvastatin and rosuvastatin produced significantly larger inhibition zones compared to simvastatin at all concentrations tested (p<0.05). The inhibition zone diameters (mm) increased with higher statin concentrations, ranging from 9 ± 1.4 to 13 ± 1.4 for atorvastatin, 8 ± 0.9 to 11 ± 0.6 for rosuvastatin, and 5 ± 1.3 to 6 ± 1.4 for simvastatin at the highest tested concentration (1200 μg/ml). SEM analysis revealed the characteristic spiral morphology of H. pylori cells. Conclusion. Statins demonstrated varying degrees of antibacterial activity against H. pylori isolates, with atorvastatin exhibiting the highest potency. While the observed effects were lower than those of conventional antibiotics, these findings suggest the potential of statins as adjunctive agents or alternative therapeutic options, warranting further investigation through in vivo studies and clinical trials.